Evaluation Of The Level Of Compliance Of Tuberculosis Patients To The Use Of Anti-Tuberculosis Drugs In Puskesmas Lima Puluh In 2023 - Marbun, Romauli Anna; Sinaga, Falentina (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
The incidence of Tuberculosis (TBC) is still a priority health problem, especially in the working area of the Puskesmas Lima Puluh . The Puskesmas Lima Puluh is a health center in the Fifty District which has a high incidence of TB, where the number of TB cases in 2022 has increased from the previous year. Patient compliance with treatment is one of the factors that determine the success of therapy. This study aims to describe the level of adherence of TB patients to the use of OAT and determine the factors that influence the level of adherence to taking OAT at the Puskesmas Lima Puluh . After the selection was carried out, 40 patients were obtained, then the probably sampling method was carried out so that 29 respondents were obtained. Data collection through direct interviews using questionnaires, bivariate and univariate data analysis. The results of statistical tests using the Chi Test showed a significant relationship with several variables including last education (p = 0.001), knowledge (p = 0.003), family support (p = 0.018) and distance traveled to health services (0.010) with adherence taking OAT in TB patients.